A Real-World, Multicenter Assessment of Drugs Requiring Weight-Based Calculations in Overweight, Adult Critically Ill Patients. (30th November 2013) - Kane-Gill, Sandra L.; Wytiaz, Nicholas P.; Thompson, Lisa M.; Muzykovsky, Karina; Buckley, Mitchell S.; Cohen, Henry; Seybert, Amy L.
Abstract : Prescribing appropriate doses of drugs requiring weight-based dosing is challenging in overweight patients due to a lack of data. With 68% of the US population considered overweight and these patients being at an increased risk for hospitalization, clinicians need guidance on dosing weight-based drugs. The purpose of this study was to identify "real-world" dose ranges of high-risk medications administered via continuous infusion requiring weight-based dosing and determine the reasons for dosing changes (ineffectiveness or adverse drug reactions). A prospective, multicenter, observational study was conducted in four intensive care units at three institutions. A total of 857 medication orders representing 11 different high-risk medications in 173 patients were reviewed. It was noted that dosing did not increase in proportion to weight classification. Overall, 14 adverse drug reactions occurred in nine patients with more in overweight patients (9 of 14). A total of 75% of orders were discontinued due to ineffectiveness in groups with higher body mass indexes. Ineffectiveness leads to dosing adjustments resulting in the opportunity for medication errors. Also, the frequent dosing changes further demonstrate our lack of knowledge of appropriate dosing for this population. Given the medications' increased propensity to cause harm, institutions should aggressively monitor these medications in overweight patients.